Using the protection motivation theory to examine the effects of fear arousal on the practice of social distancing during the COVID-19 outbreak in rural areas - Adunlin, Georges; Adedoyin, A. Christson A.; Adedoyin, Oreoluwa O.; Njoku, Anuli; Bolade-Ogunfodun, Yemisi; Bolaji, Bolanle (Journal of Human Behavior in the Social Environment, 2021)
The commentary elucidates the importance of Protection Motivation Theory (PMT) as a theoretical framework to encourage the practice of social distancing in rural areas as the world grappled with the pandemic of COVID-19 outbreak.
_eprint: https://doi.org/10.1080/10911359.2020.1783419
Keywords: COVID-19; Protection motivation theory; dept.pch; peer-reviewed; rural areas; social distancing